THE DEVELOPMENT STRATEGY OF INDONESIAN NAVAL HUMAN RESOURCES UNIT USING SWOT ANALYSIS AND INTERPRETATIVE STRUCTURAL MODELLING - Ikhwan Syahtaria; Cahyanto Cahyanto; Adi Bandono; Mukhlis Mukhlis (JOURNAL ASRO, 2021)
ABSTRACT Lapetal is an organization within the Indonesian Navy that is tasked with carrying out Navy recruitment. With the increasing number of duties and responsibilities of Lapetal and seeing the current condition of Lapetal, it is necessary to make efforts to develop Lapetal in the future. The purpose of this research is to identify the factors that influence in determining the Lapetal development strategy, determine the alternative strategy for Lapetal development, and produce a roadmap of the selected alternative strategies for Lapetal development. This study uses an integrated SWOT analysis and Interpretative Structural Modeling. SWOT analysis is used to formulate and provide alternatives in Lapetal development strategies. ISM is used to determine the priority order of the selected strategy which is then applied in making the roadmap. Based on the results of the SWOT matrix analysis, the SO Strategy consists of 6 (six) strategic steps, the ST Strategy consists of 5 (five) strategic steps, the WO Strategy consists of 8 (eight) strategic steps and the WT strategy consists of 4 (four) strategic steps. Based on weighting using the EFAS and IFAS matrices, the chosen strategy is the WO Strategy, so that the WO strategy becomes the first alternative. Based on the results of the classification of elements in the WO strategy, there are 4 (four) levels of hierarchical structure. In this hierarchical structure, it can be seen that the (WO5) and (WO6) sub-strategies are at level IV. Then the sub strategies (WO3) and (WO4) are at level III. At level II it consists of 3 (three) sub strategies, namely (WO1), (WO2), and (WO7). At level I, it is the sub strategy (WO8). The output of the SWOT and ISM analysis process in determining the Lapetal development strategy is a map or roadmap implemented in a strategic plan which is divided into five-year programs. Keywords: Lapetal, Development Strategy, SWOT, ISM, Road map